Prebiotic potential of cocoa bean shells in food industry - Blanca Lucía Botina-Azaín; Nelly Carolina Torres-Rivera; María Cristina García-Muñoz; Kelly Johana Pedroza-Berrio; Ana María Calvo-Salamanca; Yajaira Romero-Barrera; Jenny Milena Moreno-Rodríguez; Cristian Camilo Ortiz-Díaz; Olga Inés Montoya-Campusano (Cogent Food & Agriculture, 2025)
The production of cocoa beans generates millions of cocoa pods and cocoa bean shells, both of which are waste products. Cocoa bean shell (CBS), which constitutes approximately 10% of the total weight of dried cocoa beans, is known for its high bioactive compounds. It has been studied as a raw material for various industrial products, but its potential as a prebiotic has not been fully evaluated. Raw CBS and CBS fiber were obtained from fermented cocoa beans and through the chemical digestion of raw CBS, respectively. The growth of three probiotic bacteria, Lacticaseibacillus casei ATCC 393, Lactiplantibacillus plantarum ATCC 14917, and Pediococcus acidilactici ATCC 8042, were evaluated individually in culture media prepared with raw CBS and CBS fiber. This study confirms that both raw CBS and CBS fiber contain a significant amount of dietary fiber (63–65% w/w) that supports the growth of probiotic strains such as L. casei ATCC 393, L. plantarum ATCC 14917, and P. acidilactici ATCC 8042. Although these findings suggest that CBS has the potential as a prebiotic fiber, further studies are needed. The growth of L. plantarum reached a population of 108 CFU/mL within 24 hours, which is comparable to that achieved in the control medium.